Analisis pelaksanaan pemungutan Pajak Bumi Dan Bangunan Perdesaan dan Perkotaan (PBB-P2) berdasarkan Peraturan Bupati No 18 Tahun 2014 di Kecamatan Pasan Kabupaten Minahasa Tenggara - Mondigir, Vania Salsabella Christy Belina; Budiarso, Novi Swandari; Wangkar, Anneke (Yayasan Widyantara Nawasena Raharja, 2024)
Rural and Urban Sector Land and Building Tax (PBB-P2) is a tax on land and/or buildings except for areas used for plantations, forestry and mining business activities. PBB-P2 collection covers the entirSe process of registering, collecting data and assessing tax objects as well as determining, receiving payments, collecting and reporting receipts. This research aims to find out how the Land and Building Tax Collection (PBB-P2) is implemented based on Regent Regulation No. 18 of 2014 in Pasan District, Southeast Minahasa Regency. The method used in this research is a qualitative descriptive analysis method, where observations and interviews are carried out. Based on the results of existing research, it can be seen that in Pasan District, Land and Building Tax Collection (PBB-P2) has been implemented in accordance with applicable regulations, namely Regent's Regulation No. 18 of 2014 starting from registration, data collection, assessment, determination, payment, billing and recording of receipt.